Microcontroller-Based Automatic Bat Pest-Repellent Device - Candra, Rudi Arif; Ilham, Dirja Nur; Budiansyah, Arie; Harahap, Muhammad Khoiruddin (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
Bat habitats often coexist with human life, especially in homes, these mammals usually perch on the roofs of rooms or warehouses. In general, bats are parasites and pests for human life, therefore researchers have designed an automatic bat pest-repellent tool based on a microcontroller. This study aimed to create an automatic bat pest-repellent tool based on a microcontroller and electronic components as support for the circuit. This research method used three parts, namely input, output, and control. Where Arduino functioned as a controller for the entire circuit, while the ultrasonic sensor functioned as input while the Df player and speaker functioned as output. In this study, the researcher conducted 10 tests to determine the performance of the designed tool. After conducting 10 tests, the speaker produced a sound to repel bats, and the ultrasonic sensor was used as a detector of bat movements, in this test the distance of the ultrasonic sensor detected bats has been programmed, it was 5 cm to 50 cm.